2010
DOI: 10.1123/jsr.19.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Differs Between Adolescent Athletes and Adolescent Nonathletes

Abstract: Athletes reported higher scores on a number of SF-36 and PODCI subscales related to mental, emotional, and physical well-being than nonathletes. Our findings suggest that athletic involvement may be a benefit to the overall health status of adolescents and imply that athletes may be a distinct adolescent group requiring their own normative values when using the SF-36 and PODCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
135
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 30 publications
15
135
1
9
Order By: Relevance
“…Two additional studies 10,28 were identified through the hand search, resulting in a total of 8 eligible studies, which were classified into athletes and nonathletes (Table 2) and uninjured and injured athletes (Table 3). Five articles 10,28,30,33,34 met the inclusion criteria for this question. Quality scores ranged from 70.6% to 82.4% with 3 high-quality 10,33,34 (!75%) and 2 moderate-quality 28,30 studies (60%, 74.9%).…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Two additional studies 10,28 were identified through the hand search, resulting in a total of 8 eligible studies, which were classified into athletes and nonathletes (Table 2) and uninjured and injured athletes (Table 3). Five articles 10,28,30,33,34 met the inclusion criteria for this question. Quality scores ranged from 70.6% to 82.4% with 3 high-quality 10,33,34 (!75%) and 2 moderate-quality 28,30 studies (60%, 74.9%).…”
Section: Literature Searchmentioning
confidence: 99%
“…Five articles 10,28,30,33,34 met the inclusion criteria for this question. Quality scores ranged from 70.6% to 82.4% with 3 high-quality 10,33,34 (!75%) and 2 moderate-quality 28,30 studies (60%, 74.9%). The mean mDB score was 76.5% 6 5.9%.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Research showing a positive effect of physical activity on mental health among adolescents is well documented (4)(5)(6)(7)(8). A study conducted in Iceland revealed that adolescents who often practiced sports had a more positive body image and were more likely to report a healthy mental condition (9).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition, sport participation has been associated with improved parental relationships, academic performance, and self-esteem and decreased anxiety, depression, anger, and tobacco and marijuana use. 3 Although sport participation has many benefits, there are also risks, including concussions, knee injuries, and ankle sprains.…”
mentioning
confidence: 99%